Pengaruh Stress Kerja, Workload dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT.Graha Inti Permai - Ernawati Ernawati; Muhammad Asif Khan; Ery Bukhari; Muhammad Richo Rianto; Choiroel Woestho (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research is quantitative research using a questionnaire aimed at employees of PT Graha Inti Permai. Sampling in this research was carried out by distributing questionnaires with a sample size of 105 respondents. The design used in this research is hypothesis testing using the Smartpls 4.0 statistical tool. The results of this research provide an explanation that the Workload variable has a positive effect on employee performance at PT Graha Inti Permai. However, the Job Stress and Work Motivation variables have no effect on employee performance at PT Graha Inti Permai. This research shows that work stress is not the main consideration in employee performance. This research has limited research objects which were only carried out on employees of PT. Graha Inti Permai. In this research, it combines the variables of work stress, workload and work motivation on employee performance at PT. Graha Inti Permai.